Naphthenic acid fraction compounds reduce the reproductive success of wood frogs (Rana sylvatica) by affecting offspring viability. (1st January 2023) - Robinson, C.E.; Elvidge, C.K.; Frank, R.A.; Headley, J.V.; Hewitt, L.M.; Little, A.G.; Robinson, S.A.; Trudeau, V.L.; Vander Meulen, I.J.; Orihel, D.M.
Abstract: Understanding the toxicity of organic compounds in oil sands process-affected water (OSPW) is necessary to inform the development of environmental guidelines related to wastewater management in Canada's oil sands region. In the present study, we investigated the effects of naphthenic acid fraction compounds (NAFCs), one of the most toxic components of OSPW, on mating behaviour, fertility, and offspring viability in the wood frog ( Rana sylvatica ). Wild adult wood frogs were exposed separately from the opposite sex to 0, 5, or 10 mg/L of OSPW-derived NAFCs for 24 h and then combined in outdoor lake water mesocosms containing the same NAFC concentrations (n = 2 males and 1 female per mesocosm, n = 3 mesocosms per treatment). Mating events were recorded for 48 h and egg masses were measured to determine adult fertility. NAFC exposure had no significant effect on mating behaviour (probability of amplexus and oviposition, amplexus and oviposition latency, total duration of amplexus and number of amplectic events) or fertility (fertilization success and clutch size). Tadpoles (50 individuals per mesocosm at hatching, and 15 individuals per mesocosm from 42 d post-hatch) were reared in the same mesocosms under chronic NAFC exposure until metamorphic climax (61–85 d after hatching). Offspring exposed to 10 mg/L NAFCs during development were less likely to survive and complete metamorphosis, grew at a reduced rate, and displayed more frequent morphological abnormalities. These abnormalities included limb anomalies at metamorphosis, described for the first time after NAFC exposure. The results of this study suggest that NAFCs reduce wood frog reproductive success through declines in offspring viability and therefore raise the concern that exposure to NAFCs during reproduction and development may affect the recruitment of native amphibian populations in the oil sands region. Graphical abstract: Image 1 Highlights: First bigenerational and longest experimental exposure of an anuran to NAFCs. Reproductive success of frogs was reduced by a decrease in offspring viability. Negative effects were observed on larval survival, growth, and metamorphosis. Limb abnormalities were reported for the first time in NAFC-exposed metamorphs.